The “Teras Dakwah” (Dakwah Terrace) Movement Program: the Philosophy and Dakwah Activism Charity-Based in Yogyakarta - Masduki, Masduki; Triantoro, Dony Arung; Rosidi, Imron (SCAD Independent, 2022)
Dakwah in Indonesia has been growing nowadays. It is seen from the presence of preachers (da’i) and dakwah institutions and organizations in Indonesia. This article contributed to the discourse of dakwah and charity in Indonesia, especially in the social institution of Teras Dakwah in Yogyakarta. In this context, the discourse about dakwah and charity has not been much studied by previous scholars. Most studies on dakwah focus on the figure, institution, oral and written dakwah, social media, and others. The main research proposed was why and how the Teras Dakwah has been involved in charity practices in both local and regional domains. The research data were obtained based on the nethnographic study. This research showed that the involvement of the Teras Dakwah in dakwah activism-based charity was influenced by the uncertain discourse of social guarantee from the government in which in turns the Teras Dakwah was involved in providing the religious social service both local areas in Yogyakarta and regional areas outside Yogyakarta.